DAKWAH MANAGEMENT OF THE DELI SERDANG TAKLIM ASSEMBLY CONTACT AGENCY IN THE ENHANCEMENT OF THE SPIRITUAL QUOTIENT OF PERWIRITAN MOTHERS - Ravika Putri Irawan; Abdurrahman (Pena Cendekia Insani, 2025)
Management is one of the important components in the process ofda'wah activities. This research aims to examine how the da'wahmanagement conducted by BKMT Deli Serdang can enhance theSpiritual Quotient (SQ), especially among the women participatingin the recitation groups in Lubuk Pakam District, particularly inCemara Village.The type of research used in this study is thequalitative method. From the results of this research, it was foundthat the management of dakwah at BKMT Deli Serdang includesmanagement functions such as planning, organizing,implementing, and supervising.This shows a significant role inenhancing the spiritual Quotient (SQ) of the women in theperwiritan, especially in the Lubuk Pakam District. Routineactivities such as evangelism and spiritual guidance have a positiveimpact on religious awareness, good emotional management, andthe ability of mothers to build harmonious relationships with theirfamilies and social environment. dalam membangun hubungan yang harmonis dengan keluarga serta lingkungan sosial.